The Role of Teachers' Emotional Intelligence in Islamic Religious Education to Enhance Student Quality at Vocational High School - Eka Yanuarti; Ani Aryati; Riski Putra Jaya (STAI Hubbulwathan Duri, 2025)
This study investigates the role of teachers' emotional intelligence in Islamic Religious Education (PAI) learning at SMKN 4 Rejang Lebong. Emotional intelligence is essential for fostering effective learning environments and achieving educational goals, particularly in character-based education such as PAI. A qualitative descriptive approach was employed, involving the Principal, PAI teachers, and students as research participants. Data were gathered through observations, interviews, and documentation, followed by thematic analysis to explore the influence of teachers' emotional intelligence on the learning process. Findings reveal that teachers’ emotional intelligence significantly impacts students’ self-development and learning engagement. Teachers who effectively recognize and regulate emotions, manage stress, empathize, and build constructive relationships create more supportive and motivating classroom environments. This, in turn, enhances students’ academic involvement, motivation, and emotional well-being. The study underscores that emotionally intelligent teachers contribute to the formation of students’ positive character traits such as perseverance, self-confidence, and resilience. These qualities not only support academic achievement but also equip students to handle broader life challenges. The findings suggest that fostering emotional intelligence among educators is a key strategy in strengthening both student learning outcomes and character formation in Islamic education contexts.